126 A QUALITY INITIATIVE TO IMPROVE THE ASSESSMENT AND RECOMMENDATION FOR TOTAL CALCIUM INTAKE. (18th November 2021) - King, L; Pillay, I; Sayers, K; Maher, J; Ryan, S; Donnellan, C
Abstract: Background: This study assessed factors affecting adherence to calcium supplementation, estimated total calcium intake and potential to increase dietary calcium in the frail older adult. Methods: Frail Older Adults who completed a comprehensive geriatric assessment (CGA) between January—June 2021 were included. Those taking calcium supplements were telephoned by a Dietitian. Nursing home residents, hospital inpatients and those unable to complete a telephone questionnaire were excluded. A modified version of the Short Calcium Intake List (SCAIL) was used and potential to improve dietary calcium was assessed (1). Data was analysed using descriptive statistics. Results: N = 50 patients were taking a calcium supplement. N = 15 were excluded. 26 women and 9 men, aged 70 -96 yrs were included. Dietary intake ranged from 250– 1904 mg. 17% (N = 6) achieved >1, 000 mg/day dietary calcium requirements from diet. 66% (N = 23) had potential to increase their dietary calcium. 97% (N = 34) were prescribed a Calcium supplement, ranging from 500– 2000 mg/day. Total Calcium Intake including supplementation ranged from 850 mg—2, 737 mg. 82% (N = 29) exceeded their daily requirements.40% (N = 14) reported reduced compliance due to swallowing difficulties; 25%(N = 9) gastrointestinal upset; 11% (N = 4, ) taste/consistency and 8% forgetting (N = 3).Dietitian recommendations included 31% (N = 11) to stop supplementation, 34% (N = 12) to reduce, 11% (N = 4) advice on managing concerns relating to supplement and 22% (N = 8) dietary education. Conclusion: Most older adults did not meet their nutritional requirements for dietary calcium. Over two thirds could reduce or stop supplementation following dietary calcium assessment and advice. A dietary calcium estimator for the older adult, with education can be used to correct calcium intake. This modified SCAIL will be integrated into the CGA as part of a quality improvement initiative for the frail older adult. Reference: 1. Rasch L et al. (2017), Content Validity of a Short Calcium Intake List to Estimate Daily Dietary Calcium intake of Patients with Osteoporosis, Calcified Tissue International, 100(3): 271–277.